Uji Efektifitas Agensia Hayati Metarizhium anisopliae Terhadap Hama Ulat Grayak (Spodoptera litura F) Secara In Vitro - Riwan Kusmiadi; Sitti Nurul Aini; Rion Apriyadi; Ciko Ciko (Universitas Bangka Belitung, 2017)
Pests are one the reason of declined in crop production. one of them is Spodoptera litura. The purpose of this research was to determined the mortality rate of Spodoptera litura caused by M. anisopliae infection. The research is conducted at the Microbiology Laboratory of Agricultural Technology Department of the Faculty of Agriculture, Fishery, and Biology of Universitas Bangka Belitung. The research used factorial randomized block design with 2 treatment factors. The first factor ( stage larvae) consists of L1=instar 3, L2=instar 4. The second factor (the concentration) consists of V0=control, V1= 30 g/l of water, V2=35 g/l of water, V3= 40 g/l of water, V4= 45 g/l of water. The data is analyzed using ANOVA with confidence level of 95% and is further tested using the Tukey Test with the confidence level of 95%. The research results show that a concentration of 30 g/l of water and 35 g/l of water the mortality rate reaches 88,89%, while at the concentration of 40 g/l of water and 45 g/l of water the mortality rate reaches 100% with 3 to 7 days span of mortality. The larvae infected with M. anisopliae experience behavioral changes such as decreased appetite, less active movement, inactive, and transformed color to black with mycelium covering a part of the body.